Sex differences in balance among alpine ski racers: Cross-sectional age comparisons - Raschner, C.; Hildebrandt, C.; Mohr, J.; Müller, L. (Perceptual and Motor Skills, 2017)
Although balance is a key ability in the strength demands of alpine ski racing, affecting both performance and injury prevention, few studies have examined balance or related sex differences among still-maturing athletes. In this 10-year study, we investigated cross-sectional balance performances at different age periods of a representative sample of over 500 11-18-year-old elite skiers of both genders. Participants performed balance tests using the MFT S3-Check. Left-right and forward-backward movements were used to calculate sensory and symmetry balance scores, which were both incorporated into a stability score. Mann-Whitney U tests assessed gender-specific differences by age-group with a significance level set at p<.05. Results showed gender differences only on forward-backward measurements for 14-16-year-olds, with females showing better stability and sensory (but not symmetry) scores than males. Thus, gender interacted with age and maturation to influence balance ability in these participants. Additionally, these rare 10-year data support coaches in their training and talent development of maturing athletes by providing important sport-, age-, and gender-specific normative comparison data for individual trainees.